Prognostic Outcome of New-Onset Left Bundle Branch Block After Transcatheter Aortic Valve Replacement in Patients With Aortic Stenosis: A Systematic Review and Meta-Analysis - Wang, Jialu; Liu, Shidong; Han, Xiangxiang; Chen, Yang; Chen, Hao; Wan, Zunhui; Song, Bing (Frontiers in Cardiovascular Medicine, 2022)
Background: Left bundle branch block (LBBB) is a common complication of the transcatheter aortic valve replacement (TAVR), and its impact on prognosis is controversial. Methods: A comprehensive electronic search was conducted in databases (PubMed, Embase, Cochrane Library, and The Web of Science), from the date of database establishment till March 2021, to screen for studies on new-onset LBBB after TAVR. We next performed a meta-analysis to evaluate the effect of new-onset LBBB after TAVR on patient prognosis, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: A total of 17 studies, including 9205 patients, were eligible for our analysis. Patients with new-onset LBBB had elevated all-cause mortality risk verses patients without new-onset LBBB, during all follow ups. The relevant data are as follows: 30-day (RR:1.71; 95%CI:1.27–2.29; P<0.001), 1-year (RR:1.31; 95%CI:1.12–1.52; P<0.001), and 2-year (RR:1.31; 95%CI:1.09–1.56; P=0.003) follow ups. Likewise, new-onset LBBB patients also experienced increased cardiovascular mortality, compared to non-new-onset LBBB patients, but only in the 1-year follow up (RR:1.49;95%CI:1.23-1.82; P<0.001). Hospitalization for heart failure was dramatically elevated in patients with new-onset LBBB verses non-new-onset LBBB, in all follow ups. The relevant data are as follows: 30-day (RR:1.56; 95%CI:1.13–2.12; P=0.007), 1-year (RR:1.35; 95%CI:1.08–1.68; P=0.007), and 2-year (RR:1.49; 95%CI:1.21–1.84; P<0.001). Similarly, new-onset LBBB patients had higher PPI risk than non-new-onset LBBB patients, in all follow ups. The relevant data are as follows: 30-day (RR:3.05; 95%CI:1.49–6.22; P=0.002), 1-year (RR:2.15;95%CI:1.52–3.03;P<0.001), and 2-year (RR:2.52;95%CI:1.68–3.78;P<0.001). Conclusion: Patients with new-onset LBBB have worse prognosis after TAVR than those without new-onset LBBB. Recognition of the adverse effects of post-TAVR new-onset LBBB can lead to the development of new strategies that enhance clinical outcomes.